A new calibration setup for lock-in amplifiers in the low frequency range and its validation in a bilateral comparison. (19th February 2021) - Cultrera, Alessandro; Corminboeuf, David; D'Elia, Vincenzo; Tran, Ngoc Thanh Mai; Callegaro, Luca; Ortolano, Massimo
Abstract: This paper addresses the calibration of lock-in amplifiers in the low frequency range. A simple but effective calibration setup implemented at INRIM is described. This includes a stable low-voltage source, composed of a digital sine wave generator and a cascade of two voltage dividers, one inductive and one resistive. The magnitude error is the lock-in magnitude error, which can be determined with an uncertainty of the order of 10 −4 or better, that is, two orders of magnitude lower than the typical lock-in accuracy specification. The system can operate with an input voltage from 0.1 µV to 10 µV and a frequency from a few hertz to about 1 kHz. The performances of the calibration setup were evaluated at 1 µV and 10 μV at 20 Hz and 103 Hz and compared with those of another existing setup, implemented at METAS, through a direct comparison in the framework of an EURAMET research project.